2009
DOI: 10.1016/j.ejphar.2008.12.021
|View full text |Cite
|
Sign up to set email alerts
|

The selective non-peptidic delta opioid agonist SNC80 does not facilitate intracranial self-stimulation in rats

Abstract: Delta opioid receptor agonists are under development for a variety of clinical applications, and some findings in rats raise the possibility that agents with this mechanism have abuse liability. The present study assessed the effects of the non-peptidic delta opioid agonist SNC80 in an assay of intracranial self-stimulation (ICSS) in rats. ICSS was examined at multiple stimulation frequencies to permit generation of frequency-response rate curves and evaluation of curve shifts produced by experimental manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 39 publications
3
39
0
Order By: Relevance
“…These blunted Max Rates normalized during the remaining passes. Decreased Max Rates can be the result of decreased hedonic value of stimulation (Do Carmo et al, 2009) or reduced performance ability (Carlezon and Chartoff, 2007). The time-course of these effects are consistent with our previous findings using central (Bechtholt-Gompf et al, 2010) or intra-cortical infusions of DHK (John et al, 2012).…”
Section: Effects Of Dhk On Icsssupporting
confidence: 80%
See 1 more Smart Citation
“…These blunted Max Rates normalized during the remaining passes. Decreased Max Rates can be the result of decreased hedonic value of stimulation (Do Carmo et al, 2009) or reduced performance ability (Carlezon and Chartoff, 2007). The time-course of these effects are consistent with our previous findings using central (Bechtholt-Gompf et al, 2010) or intra-cortical infusions of DHK (John et al, 2012).…”
Section: Effects Of Dhk On Icsssupporting
confidence: 80%
“…We extend the previous literature by showing that blockade of astrocytic glutamate reuptake specifically in the CEA can induce anhedonia. The present findings also suggest that intra-CEA DHK has profound effects on maximum response rates in the ICSS paradigm, which can be indicative of decreased motivation or an anhedonic-like effect (Bechtholt-Gompf et al, 2010), as either decreasing the intensity of the stimulation or increasing the response requirement decreases maximum response rates (Do Carmo et al, 2009). Previous reports have shown that increased glutamate levels in the amygdala can induce other signs of depression such as social avoidance and disrupted circadian rhythms in rats (Lee et al, 2007).…”
Section: Discussionmentioning
confidence: 54%
“…Kappa and Delta Opioids. Selective kappa opioid receptor agonists such as U50,488 (5,6-dimethoxy-N, N-dipropyl-2,3-dihydro-1H-inden-2-amine), U69,593 [Nmethyl-2-phenyl-N-[(5R,7S,8S)-7-(pyrrolidin-1-yl)-1-oxaspiro[4.5]dec-8-yl]acetamide], and salvinorin A produce a dose-dependent depression of ICSS (Todtenkopf et al, 2004;Carlezon et al, 2006;Dinieri et al, 2009;Do Carmo et al, 2009;Negus et al, 2010Negus et al, , 2012aRussell et al, 2013). For example, Fig.…”
Section: B Opioidsmentioning
confidence: 99%
“…After initial shaping of lever press responding, rats were trained under a continuous reinforcement schedule of brain stimulation by using procedures similar to those described previously (Carlezon and Chartoff, 2007;Do Carmo et al, 2009;Negus et al, 2010a). During sessions lasting 30 to 60 min, each lever press resulted in the delivery of a 0.5-s train of square wave cathodal pulses (0.1-ms pulse duration), and stimulation was accompanied by illumination of the stimulus lights over the lever.…”
Section: Assay Of Intracranial Self-stimulationmentioning
confidence: 99%